Acute liver injury and diffuse subcutaneous pneumatosis following compound paracetamol and amantadine hydrochloride tablets poisoning: a case report - Zhao, Zhiwen; Wang, Bo; Cai, Lanlan; Liu, Xuefang; Fang, Zhicheng (Frontiers in Pharmacology, 2025)
IntroductionSevere acute poisoning from Compound paracetamol and Amantadine hydrochloride tablets can result in various complications, including acute liver injury, central nervous system reactions, and gastrointestinal symptoms.Case summaryA 15-year-old previously healthy female ingested 108 Compound paracetamol and Amantadine hydrochloride tablets. She presented to the emergency department with severe nausea, vomiting, abdominal pain, and distension, along with confusion. Emergency interventions, including gastric lavage and endotracheal intubation for respiratory support, were initiated. She was subsequently transferred to the intensive care unit for advanced life support, including nasogastric tube, hemoperfusion, and hemodialysis. During treatment, she developed coagulation abnormalities, liver injury, acute gastric mucosal bleeding, electrolyte imbalances, and psychiatric symptoms. A computed tomography (CT) scan revealed diffuse subcutaneous pneumatosis extending to the neck, anterior chest wall, thoracic cavity, and mediastinum. Following aggressive treatment, the patient was successfully discharged on the seventh day after the overdose.ConclusionAcute liver injury and diffuse subcutaneous pneumatosis affecting multiple regions, caused by the ingestion of a large quantity of Compound paracetamol and Amantadine hydrochloride tablets, is a rare occurrence. With early gastric lavage, blood purification, and supportive therapy, the patient was successfully treated and discharged.